Zirconium-based cubic-perovskite materials for photocatalytic solar cell applications: a DFT study - Shahzad, Muhammad Khuram; Mujtaba, Syed Taqveem; Hussain, Shoukat; Rehman, Jalil Ur; Farooq, Muhammad Umair; Khan, Muhammad Aslam; Tahir, Muhammad Bilal; Mahmood, Muhammad Ali (RSC advances, 2022)
The structural, electronic, optical, and mechanical characteristics of the cubic inorganic perovskites XZrO 3 (X = Rb and K) based on Rb and K were studied using Cambridge Serial Total Energy Package (CASTEP)-based density functional theory (DFT) via the ultrasoft pseudo-potential (USP) plane wave and generalized gradient approximation (GGA)-Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional. The measured lattice parameters are 3.55 Å and 4.23 Å, and the band gaps of RbZrO 3 and KZrO 3 are 3.57 eV and 3.78 eV, respectively. Our results indicate that the compounds have indirect and wide bandgaps, making them useful for improving conductivity. It is observed that the compounds have anisotropic, ductile, and brittle natures. The anisotropic factor values of RbZrO 3 and KZrO 3 are 0.67067 and 0.87224, and their Poisson's ratios are 0.27356 and 0.25853, respectively. In terms of optical properties, they exhibited high optical absorption and conductivity and were active in the visible region for solar cell applications. These results indicate that they could be highly useful for light-emitting diodes (LEDs) and other reflection purposes owing to their indirect bandgap. The results of our investigation of RbZrO 3 and KZrO 3 present them as favorable materials for solar cell and LED applications. The structural, electronic, optical, and mechanical characteristics of cubic inorganic perovskites XZrO 3 (X = Rb and K) were studied using the Cambridge serial total energy package-based DFT.